Development of APE Jemari Keahlian to Develop Cognitive Abilities in Children 4-5 Years Old - Nur Laela, Minatul; Ayu Ashari, Fitri; Dwi Nurcahyani, Listya; Rusmilawati, Novi; Bin Ishak, Zahari (Indonesian Journal of Early Childhood Educational Research (IJECER), 2022)
Cognitive is one aspect that needs to be developed from an early age. To develop these abilities, it is necessary to make efforts, one of which is by using educational game tools with the fingers of expertise. This study aims to determine the development of cognitive abilities using APE. The development of cognitive abilities is given to children aged 4-5 years with a sample of 6 children. The research method used is using R&D (Research and development). Data were collected and analyzed using SPSS rocks with the Wilcoxon signed test. This test is carried out after the pre-test and post-test on the child and then tested. This studyÔÇÖs results indicate significant differences in children when they are given treatment and have not been treated. Thus, the development of this APE Jemari keahlian can improve the cognitive abilities of early childhood.┬á